2009
DOI: 10.1111/j.1748-5827.2008.00657.x
|View full text |Cite
|
Sign up to set email alerts
|

Ketone measurements using dipstick methodology in cats with diabetes mellitus

Abstract: The urine and plasma ketone dip tests have a different diagnostic accuracy, and results have to be interpreted differently. Because of its high sensitivity, the plasma ketone dip test performs better than the urine ketone dip test to identify cats with impending or established ketoacidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1
12

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 16 publications
2
20
1
12
Order By: Relevance
“…Proposed methods to detect the increase of ketone bodies include 3-HB measurement with laboratory methods [7], which is not practical in emergency settings, the determination of urinary or plasma AcAc with dip stick methods [3,31,32], and the detection of 3-HB using a hand-held ketone sensor [6,14,29]. The detection of urinary AcAc is the most commonly used method, but many studies have demonstrated that this test is associated with a considerable risk of false-positive and false-negative results [3,31,32]. Based on the severity of the disease, a false positive result is less dangerous because the disease can then be excluded by the blood gas analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Proposed methods to detect the increase of ketone bodies include 3-HB measurement with laboratory methods [7], which is not practical in emergency settings, the determination of urinary or plasma AcAc with dip stick methods [3,31,32], and the detection of 3-HB using a hand-held ketone sensor [6,14,29]. The detection of urinary AcAc is the most commonly used method, but many studies have demonstrated that this test is associated with a considerable risk of false-positive and false-negative results [3,31,32]. Based on the severity of the disease, a false positive result is less dangerous because the disease can then be excluded by the blood gas analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a false negative result may result in underestimation of the patient's ketotic state and consequent misdiagnosis of the DKA. Based on a study conducted by Zeugswetter and Pagiz [32], the determination of plasma ketones by the dipstick test appears to have a greater sensitivity than the urinary ketone test and therefore to be a useful tool to rule out DKA. Both tests only detect the presence of AcAc in urine or plasma samples and not the presence of 3-HB; furthermore, the measurement of plasma ketones by the dipstick test is associated with false positive results [3,32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8-6), or plasma from heparinized hematocrit tubes can be used to test for the presence of acetoacetate using urine reagent strips used to document ketonuria (Duarte et al, 2002;Brady et al, 2003;Hoenig et al, 2008;Di Tommaso et al, 2009;Zeugswetter and Pagitz, 2009). Measurement of the blood glucose concentration using a portable blood glucose monitoring device (see Protocol for Generating the Serial Blood Glucose Curve in the Hospital in Chapter 6) and testing for the presence of glycosuria using urine reagent test strips (e.g., Keto-Diastix) allows the rapid confirmation of diabetes mellitus.…”
Section: Establishing the Diagnosis Of Diabetic Ketosis And Ketoacidosismentioning
confidence: 99%